Design and Material Analysis of a Suspension System in Scooter by using Finite Element Analysis Method - K, Sathishkumar; G, Dinesh (International Research Journal of Multidisciplinary Technovation, 2019)
The principle part for a vehicle suspension is the compression spring system, which is fabricated for arresting shock impulse. Suspension system work on the principle of fluid transformation between compression and expansion cycle. Mostly the suspension system is used in motorcycles for providing better handling, prompt braking, safety, and comfort by keeping the passengers isolated from road noise, bumps, and vibration. The shock absorbers duty is to absorb or dissipate energy. In a vehicle, it reduces the effect of traveling over rough ground, leading to improved ride quality, and increase in comfort due to the substantially reduced amplitude of disturbances. In most of the cases, the spring which is used in the scooter suspension system is made up of beryllium copper, phosphor bronze and titanium, but in this research paper a scooter suspension system is designed and the designed suspension system is analyzed using ansys with different material properties. The composite material gives less deformation because of the high stiffness to load carrying capacity. So the Composite suspension system is recommended for two and three-wheeled vehicles.